Digital Transformation of MSMEs as a Competitiveness Enhancement Strategy in the Digital Economy Era - Ayu, Diah Pajar; Suryanto, Jonatan Dedi; Afriyanto, Genta; Ulfah, Fadilla; Soleh, Ahmad (The Future of Education Journal, 2026)
The advancement of the digital economy encourages micro, small, and medium enterprises (MSMEs) to adapt in order to remain competitive amid increasingly intense market competition. However, many MSMEs in Indonesia have not yet utilized digital technology optimally due to limited access to training and low levels of digital literacy. This study aims to examine the role of digital transformation as a strategy for strengthening MSME competitiveness in the digital economy era. This research employed a qualitative approach using a library research method, in which secondary data were obtained through the review of various scientific journals, research reports, and academic publications relevant to digital transformation and MSME development. The findings indicate that digital transformation contributes significantly to enhancing MSME competitiveness through three main dimensions: operational efficiency, expanded market access through e-commerce and social media, and strengthened business resilience. Nevertheless, challenges such as limited human resource capacity and weak supporting ecosystems remain major obstacles. The implications of this study highlight the need for synergy among business actors, government institutions, and training organizations to create a conducive digital ecosystem for the sustainable growth of MSMEs.